The Translationally Controlled Tumor Protein (TCTP), a Novel Antigen of Babesia bovis, Participates in the Establishment of Acute Infection and Contains Neutralizing B-Cell Epitopes - Chyntia Pérez-Almeida; Diego Josimar Hernández-Silva; Edwin Esaú Hernández-Arvizu; Masahito Asada; Shin-ichiro Kawazu; Massaro W. Ueti; José Guadalupe Gomez-Soto; Urso Martín Dávila-Montero; Carlos A. Vega y Murguía; Juan Mosqueda (Pathogens)
Babesia bovis is a protozoan parasite that causes babesiosis in cattle. It has been hypothesized that in apicomplexan parasites, translationally controlled tumor protein (TCTP) interferes with the host immune response by inhibiting B cell proliferation. The aim of this study was the characterization of B. bovis TCTP (BboTCTP) and the evaluation of its expression, immunogenicity and role in infection. The tctp gene was identified and sequenced from B. bovis isolates and revealed a high conservation. Expression was confirmed in intraerythrocytic stages by Western blot and confocal microscopy. Synthetic peptides containing predicted B cell epitopes were used to immunize cattle, followed by a challenge with a virulent B. bovis strain. Immunized animals showed milder clinical signs and faster recovery compared to controls. Sera from non-immunized animals exhibited lower total IgG levels after challenge (p < 0.05), while sera from immunized animals induced significant in vitro invasion inhibition (32–33%). These results suggest that BboTCTP is immunogenic and may play a role in modulating the host immune response. The results provide novel insights into B. bovis biology and support BboTCTP as a promising candidate for further evaluation as a vaccine antigen. Future studies should explore its immunomodulatory mechanisms and potential use in combined vaccine formulations.